OPEN BANKING API IMPLEMENTATION: IMPLICATIONS FOR FINANCIAL SERVICES COMPETITION AND INNOVATION - Rosa Fitriana; Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The implementation of Open Banking API has become a major catalyst in the transformation of the financial industry, especially in Indonesia, by encouraging open and secure integration of financial data between banks, fintech, and other industry players. Through standardisation such as SNAP initiated by Bank Indonesia, Open Banking API strengthens collaboration and healthy competition, thus spurring the creation of various digital financial service innovations, ranging from financial management applications, account aggregators, to data-driven payment and loan services. However, behind these opportunities, there are significant challenges related to data security, consumer protection, as well as infrastructure readiness and adaptive regulations. This research uses a literature review method to analyse the implications of Open Banking API implementation on the dynamics of financial services competition and innovation, and highlights the importance of policy harmonisation, improved digital literacy and strengthened governance to ensure an inclusive, efficient and highly competitive digital financial ecosystem in Indonesia.